Pelatihan Perhitungan HPP dalam Menentukan Harga Jual Bagi Anggota Koperasi Bina Bersama Syariah Kecamatan Ranto Peureulak Kabupaten Aceh Timur - Jamali; Jamil, Muhammad; Zubaili; Zulkarnaini (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
This activity aims to provide a common understanding between managers and members in the COGS Calculation training in determining the selling price for members of the Bina Bersama Syariah Cooperative, Ranto Peureulak District, East Aceh Regency at MAN 3 Aceh Timur in order to increase knowledge and its application in calculating Cost of Goods Sold and determining good and correct selling price by using various methods of calculating the selling price. The location of community service activities is carried out through face-to-face meetings at MAN 3 Aceh Timur. Community Service Activities use the demonstration method, giving material by mentors, discussing with participants, and each group demonstrating the results of calculating the Cost of Goods Sold report and determining the price. The results of the activity provide knowledge and understanding for participants while still paying attention to the development of the purchase price for each item to be sold, the results of observations and analyzes of the data obtained from the Bina Bersama Syariah Cooperative. After discussing and discussing the problem, the author concludes that the calculation of the cost of goods sold to determine the selling price of the Bina Bersama Syariah Cooperative has gone quite well.